2011
DOI: 10.1111/j.1349-7006.2011.01928.x
|View full text |Cite
|
Sign up to set email alerts
|

hOGG1 Ser326Cys polymorphism and risk of childhood acute lymphoblastic leukemia in a Chinese population

Abstract: Oxidative DNA damage caused by reactive oxygen species can produce 8-oxoguanine (8-oxoG) in DNA, which is misread and leads to G:C fi T:A transversions. This can be carcinogenic. Repair of 8-oxoG by the base excision repair pathway involves the activity of human 8-oxoG DNA glycosylase 1 (hOGG1). Accumulating evidence suggests that the hOGG1 Ser326Cys polymorphism affects the activity of hOGG1 and might serve as a genetic marker for susceptibility to several cancers. To determine whether this polymorphism is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…This may be another example of the inverse relationship between age-dependent degenerative disease and cancer, brought about by a lifelong compromise between accuracy of identification and repair of damage and the propensity to route damaged cells to apoptosis. Interestingly, children carriers of Cys/Cys genotypes by the Ser326Cys polymorphism of hOGG1 were identified to be at increased risk of development of ALL than carriers of at least one Ser allele, [131] supporting the hypothesis that the risk of LONDD was associated with decreased risk of most cancers except for those that originated from cells with differentiation blocks (as is ALL).…”
Section: Cancer and Londd: Extremes Of A Wide Spectrum?mentioning
confidence: 60%
“…This may be another example of the inverse relationship between age-dependent degenerative disease and cancer, brought about by a lifelong compromise between accuracy of identification and repair of damage and the propensity to route damaged cells to apoptosis. Interestingly, children carriers of Cys/Cys genotypes by the Ser326Cys polymorphism of hOGG1 were identified to be at increased risk of development of ALL than carriers of at least one Ser allele, [131] supporting the hypothesis that the risk of LONDD was associated with decreased risk of most cancers except for those that originated from cells with differentiation blocks (as is ALL).…”
Section: Cancer and Londd: Extremes Of A Wide Spectrum?mentioning
confidence: 60%
“…In particular, associations with the Ser326Cys polymorphism have been reported for different cancers, such as smoking-associated lung cancer, gall-bladder cancer and lymphoblastic leukemia [16][17][18]; however, a meta-analysis suggested that the variant 326Cys allele would play a significant protective effect against breast cancer in European women [19]. In a recent study by our group we have not found associations between this SNP and DTC incidence [20].…”
Section: Discussionmentioning
confidence: 83%
“…were iden fied to be at decreased risk for development of acute childhood lymphoblas c leukemia [130]. Carriership of polymorphisms in BER genes is associated with suscep bility to Grave's disease, a toxic hyperfunc on of the thyroid gland that affects virtually all organs and systems.…”
Section: Neil Genesmentioning
confidence: 99%